2010
DOI: 10.1080/01635580903532457
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Abrogate the Anticarcinogenic Effect of Eicosapentaenoic Acid in Atm-Deficient Mice

Abstract: Recent studies have demonstrated that n-3 polyunsaturated fatty acids such as eicosapentaenoic acid (EPA) are able to suppress cell proliferation and inhibit tumor growth. The objective of our study was to investigate the influence of a high dose EPA on the development of the tumor phenotype in ataxia-telangiectasia mutated (Atm)-deficient mice, a genetic cancer model that is associated with increased levels of oxidative stress. We analyzed toxicity, proliferation, cell-cycle progression, and apoptosis of EPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…High intake of n-3 fatty acids diminishes the chemotactic responsiveness of neutrophils and monocytes ( 25 ) and decreases the production of free radicals ( 26 ). Some studies have concluded that there are some benefits of fish oil in oxidative damage to DNA ( 27 - 30 ). However, a recent study reported that EPA treatment in Atm-deficient mice led to the formation of reactive oxygen species and the accumulation of oxidative DNA damage ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…High intake of n-3 fatty acids diminishes the chemotactic responsiveness of neutrophils and monocytes ( 25 ) and decreases the production of free radicals ( 26 ). Some studies have concluded that there are some benefits of fish oil in oxidative damage to DNA ( 27 - 30 ). However, a recent study reported that EPA treatment in Atm-deficient mice led to the formation of reactive oxygen species and the accumulation of oxidative DNA damage ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies at the University of Tromso in Norway have shown that the industrial processes used to extract fish oil destroy or remove the trace ingredients in fish (such as the polyphenols) that likely played a critical role in conferring their original health benefits and certainly greatly reduced anti-inflammatory effects of the oil (Elvevoll, Osterud, 2003). In fact, the removal of antioxidants and other trace compounds creates a situation where the purified fish oils can become pro-oxidative (Sanders, hinds, 1992;Sen et al, 1997;Umegaki et al, 2001; Vericel at al., 2003; Schubert et al, 2010), pro-inflammatory (Mata et al, 1996;berstad et al, 2003), and cause increased DNA damage (Schubert et al, 2010). Worryingly, there is evidence that older subjectsthe bulk of those who take ω3 supplements -are intrinsically more vulnerable to its pro-oxidative effects (cazzola et al, 2007) probably because they are not eating enough of the appropriate antioxidants to compensate for the ω3's (Umegaki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In certain situations such as heavy exercise, 8 high purified o3 highly unsaturated fatty acids intakes, 10,11,13 insufficient antioxidant cover 8,9 and significant pre-existing oxidative stress and/or inflammatory pathology, 8,13 this may create a pro-inflammatory environment, manifesting inter alia with increased DNA damage 9 and increased levels of soluble vascular cell adhesion molecule (sVCAM-1). 13 It is important to point out that others have found sVCAM-1 to be reduced; 15 the divergent findings may reflect different intakes of dietary ancillary factors in different populations.…”
Section: Too Pure To Be True?mentioning
confidence: 99%